The Role of Work Motivation and Job Satisfaction in Improving Employee Productivity - Permatasari; Firmansyah; Wijayanti (Economy, Business, Finance, Accounting & Management Journal, 2025)
This study aims to analyze the role of work motivation and job satisfaction in improving employee productivity within an organization. Work motivation is an internal factor that drives individuals to perform optimally in achieving organizational goals, while job satisfaction reflects employees’ level of comfort and positive feelings toward their work. The research method employed is a quantitative approach, with data collected through the distribution of questionnaires to employees. The data obtained were analyzed using statistical techniques to test the influence of work motivation and job satisfaction on employee productivity. The results indicate that work motivation and job satisfaction have a positive and significant influence on employee productivity, both partially and simultaneously. Employees with high motivation and good job satisfaction tend to demonstrate more effective and efficient performance and are able to achieve work targets optimally. These findings indicate that organizations need to pay attention to aspects of work motivation and job satisfaction through policies that support career development, the provision of rewards, and the creation of a conducive work environment to sustainably improve employee productivity